Conference Review: Fibres in Early Textiles, Glasgow 2019 - Alistair Dickey (EXARC Journal, 2019)
The 16th conference of the Early Textiles Study Group was held at the University of Glasgow, Scotland, from 6th to 7th June, 2019. The theme for the biennial conference, Fibres in Early Textiles from Prehistory to AD 1600, was attended by almost sixty enthusiastic participants, and there was a strong international feel to the gathering. Attendees came from a diverse range of backgrounds, including university academics, postgraduate researchers, independent researchers, commercial archaeologists, textile foundation representatives, and museum and craft specialists.